175k views
1 vote
Please clink on the link. Don’t give me fake answers or links or you will be reported.

Please clink on the link. Don’t give me fake answers or links or you will be reported-example-1
User Souperman
by
5.0k points

2 Answers

1 vote

Answer:

it's B

Explanation:

(x + 5)^2 + (y - 2)^2 = 81

A. is not A

(1 + 5)^2 + (-4 - 2)^2

6^2 + -6^2

36 + (-36) = 0

B. is B

(-5 + 5)^2 + (11 - 2)^2

0^2 + 9^2

0 + 81 = 81

C. is not C

(-5 + 5)^2 + (2 - 2)^2

0^2 + 0^2

0 + 0 = 0

D. is not D

(-3 + 5)^2 + (-8 - 2)^2

2^2 + -10^2

4 + -100 = -98

User Frenetix
by
5.5k points
5 votes
D is the correct answer
User Ktec
by
5.4k points